COMPETENCY-BASED HUMAN RESOURCE MANAGEMENT STRATEGIES TO BUILD COMPETITIVE ORGANIZATIONS - lfani, Elsa Nur A; Ma’ruvah, Lailatul; Salsabillah, Faridah; Rahmatullah, M. Imam; Sungkar, Rakay Abdullah; Hadiati, Eti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research discusses competency-based human resource management (MSDM) as a strategy for building a competitive organization through literature study methods relating to methods of collecting library data, reading and taking notes, as well as managing research data objectively, systematically, analytically and critically. Competency-based MSDM is an approach that emphasizes adapting employee skills, knowledge and attitudes to the company's strategic needs. In this research, the meaning of competency-based MSDM is discussed, the stages of implementation, the importance of this approach, and the strategic role in creating competitive advantage. Literature analysis shows that competency-based MSDM helps organizations develop human resource development strategies that are aligned with business goals, which ultimately increases employee productivity and organizational competitiveness. The results of this research also emphasize the importance of competency-based MSDM in increasing organizational adaptability, building a productive work culture, and strengthening competitive advantages in the global market. Thus, a competency-based MSDM strategy is a key element for organizations that want to survive and excel in dynamic competition